PETRE T. FRANGOPOL (1933-2020). ROMANIAN ACADEMIC, SCIENTIST, MENTOR AND FRIEND - BENGA, Gheorghe (Studia Universitatis Babeș-Bolyai Chemia, 2021)
In December 2020, academics and scientists – particularly chemists – received the very sad news that our beloved colleague and friend Petre T. Frangopol passed away. The aim of this obituary is to pay tribute to an outstanding Romanian scientist, a man of great character and an unforgettable friend. Petre T. Frangopol (a.k.a. Petrache for his friends) described in detail the history of his family in a Meeting of the Romanian Academy (October 8, 2018) dedicated to his 85th anniversary. I had the honor to be invited speaker to that event, as we collaborated for several decades. The proceedings of that Meeting were published [1, 2].